Gambaran Tingkat Kelelahan (Burnout) Pada Mahasiswa DIII Keperawatan Semester 5 Dalam Pembelajaran Daring di Masa Pandemi COVID-19 di Denpasar - I Gusti Ayu Ngurah Pradnya Trisnawati; Ni Luh Putu Suardini Yudhawati; Ni Made Sri Muryani; I Kadek Artawan (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: Fatigue (Burnout) is a psychological syndrome in a person that causes fatigue, emotional and mental stress due to excessive stress which can be caused by stressful situations that must be resolved beyond the individual's ability with symptoms such as decreased interest in learning, decreased enthusiasm and fatigue. A person's burnout varies depending on a person's ability to deal with difficult situations that cause fatigue, depersonalization and according to him the interest in self-achievement in certain situations. The results of previous this study showed that most of the respondents, which were 88 respondents (56.4%) experienced moderate fatigue. The purpose of this study is to describe the level of fatigue (Burnout) in the 5th semester of diploma 3 nursing students in online learning during the 2019 coronavirus disease pandemic in Denpasar. Methods: This research is a quantitative research with a cross sectional study. Sampling was total sampling by using 65 people, who were the 5th semester of diploma nursing students at the Campus of Stikes KESDAM IX / Udayana and ITEKES. The instrument used was the MBI-SS questionnaire from Maslach and Jakson which was adopted from previous research and has been validated to determine the level of student burnout, using an online questionnaire with the Google form. Data analysis in this study used univariate analysis. Results: The results of this study showed that most of the respondents, which were 49 respondents (75.4%) experienced moderate fatigue. Characteristics of respondents based on age as many as 65 people (100%) aged > 20 years, characteristics of respondents based on gender where most of the respondents as many as 36 respondents (55.4%) were female. Conclusion: Most of the respondents have moderate levels of fatigue (burnout)